(untitled) (Bangladesh Journal of Urology, 2020)
Objectives: To find out any changes in renal function in donor following kidney donation. Materials and Methods: A Hospital based prospective study was conducted in the Department of Urology of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from April 2011 to September 2012, Investigations included specific gravity and urinary microalbumin, ultrasonogram of kidneys, serum creatinine, estimated glomerular filtration rate. According to inclusion and exclusion criteria a total of 37 donors were enrolled in this study. Subsequent follow up were taken at the end of three months, six months and nine months. Data were evaluated by Paired t-test, Significance was defined p value<0.05. Results: The age range varied from 25 to 39 years and almost a half (45.9%) of patients had age belonged to 25-30 years and male to female ratio was 1:2.4. The mean baseline specific gravity was 1016.97±8.03, serum creatinine 1.03±0.24. The baseline urinary microalbumin was found nil and subsequent 1st,2nd, and 3rd follow up were also nil. The mean difference of specific gravity, serum creatinine (mg/dl) and GFR estimated by cretainine clearance rate and DPTA were almost consistent between baseline and the subsequent follow-up, no statistical significant (P>0.05) was found between baseline and the subsequent follow-up. Conclusion: Renal function of the remaining kidney in living donors does not significantly change after donor nephrectomy. Bangladesh Journal of Urology, Vol. 19, No. 1, Jan 2016 p.18-22